2015
DOI: 10.1111/jnc.13056
|View full text |Cite
|
Sign up to set email alerts
|

Tripchlorolide improves cognitive deficits by reducing amyloid β and upregulating synapse‐related proteins in a transgenic model of Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is characterized by early impairments in memory and progressive neurodegeneration. Disruption of synaptic plasticity processes that underlie learning and memory contribute partly to this pathophysiology. Tripchlorolide (T 4 ), an extract from a traditional Chinese herbal Tripterygium wilfordii Hook F, has been shown to be neuroprotective in animal models of Parkinson's disease and to improve cognitive deficits in senescence-accelerated mouse P8. In this study, we investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 62 publications
(65 reference statements)
3
30
0
1
Order By: Relevance
“…Synaptic loss is one of the neuropathological hallmarks of AD, and synaptophysin and PSD-95 are the markers of the pre- and post-synapse, respectively. Compelling evidence has shown that the levels of PSD-95 and synaptophysin are reduced in AD transgenic mouse models[ 27 , 28 ] and in brains from AD patients[ 29 ]. In this study, we first tested the expression of PSD-95 and synaptophysin in the hippocampus of AD mice.…”
Section: Resultsmentioning
confidence: 99%
“…Synaptic loss is one of the neuropathological hallmarks of AD, and synaptophysin and PSD-95 are the markers of the pre- and post-synapse, respectively. Compelling evidence has shown that the levels of PSD-95 and synaptophysin are reduced in AD transgenic mouse models[ 27 , 28 ] and in brains from AD patients[ 29 ]. In this study, we first tested the expression of PSD-95 and synaptophysin in the hippocampus of AD mice.…”
Section: Resultsmentioning
confidence: 99%
“…Synapse-related proteins constitute the structural and functional foundation of synapses. However, the expression levels of synapse-related proteins, such as synaptophysin, PSD-95, p-CaMKII, and p-CREB, are significantly decreased in the cortex and hippocampus of AD patients and of an AD mouse model (Gylys et al, 2004; Almeida et al, 2005; Zeng et al, 2015). Moreover, synaptic loss is the most severe condition of synaptic injury, and it manifests as the loss of dendritic spines and synapses in the brains of a transgenic AD mouse model and of AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…These mice exhibit AD-related pathology earlier than other animal models, and amyloid deposition starts in the deep cortex and subiculum at 2 months of age. Synaptic marker proteins decrease at 4–9 months, and memory deficits are detected from 4–6 months of age [ 19 20 ]. Animal treatment and maintenance were performed in accordance with the Animal Care and Use Guidelines of Seoul National University, Seoul, Korea.…”
Section: Methodsmentioning
confidence: 99%